2020
DOI: 10.18632/aging.103338
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits the malignant progression of hepatocellular carcinoma via MARCH1-induced regulation of PTEN/AKT signaling

Abstract: Resveratrol is a common, naturally occurring polyphenol confirmed with inhibited the cellular effects of carcinogenesis. However, the molecular mechanism underlying resveratrol's action against hepatocellular carcinoma (HCC) is still unclear. In addition, MARCH1 promotes the initiation and progression of HCC, but it is unclear whether resveratrol exerts antitumor efforts by regulating MARCH1 expression. This study determined the molecular mechanisms underlying the antitumor effects of resveratrol in HCC. Resve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Meanwhile, MK2206 (an AKT inhibitor) and bisperoxovanadium (BPV; a PTEN inhibitor) combined with resveratrol decreased MARCH1 expression more than the singletreatment HCC group. These results suggested that resveratrol affects the biological characteristics of HCC via downregulation of MARCH1 expression (Dai et al, 2020).…”
Section: Resveratrolmentioning
confidence: 82%
“…Meanwhile, MK2206 (an AKT inhibitor) and bisperoxovanadium (BPV; a PTEN inhibitor) combined with resveratrol decreased MARCH1 expression more than the singletreatment HCC group. These results suggested that resveratrol affects the biological characteristics of HCC via downregulation of MARCH1 expression (Dai et al, 2020).…”
Section: Resveratrolmentioning
confidence: 82%
“…Interestingly, SIN down-regulated the MARCH1 protein expression but increased MARCH1 transcription in HepG2 cells. MG132, as a proteasome inhibitor Dai et al (2020) , rescues MARCH1 protein expression in HepG2 cells after SIN treatment. Therefore, SIN-induced MARCH1 down-regulation through proteasomal degradation.…”
Section: Discussionmentioning
confidence: 98%
“…Our Lab found that MARCH1 was over-expressed in HCC cells and tissues, and promoted the proliferation of HCC cells. MARCH1 downregulation induced by siRNA or drugs could inhibit the progression of HCC by down-regulating PI3K-AKT-β-catenin and PTEN/AKT signaling pathways ( Xie et al, 2019a ; Xie et al, 2019b ; Dai et al, 2020 ). However, the molecular mechanism of SIN in inhibiting MARCH1 expression and its downstream signaling molecules is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo experiments have also suggested that MARCH1 may be a potential oncogene in liver cancer [11]. Other studies have found that resveratrol affected the biological characteristics of liver cancer by downregulating the expression level of MARCH1 [13]. In contrast, MARCH1 exerted a tumor suppressor effect in bladder cancer, and ciRs-6 increased the expression level of MARCH1 by sponge adsorption of miR-653 to inhibit the growth of bladder cancer [12].…”
Section: Discussionmentioning
confidence: 99%